Design patterns Java workbook - Metsker, Steven John (Software patterns series., 2002)
Praise for Design Patterns Java Workbook "An excellent book... I'm incredibly impressed with how readable it is. I understood every single chapter, and I think any reader with any Java familiarity would. This book is going to be required reading in a lot of places, including my office." - Joshua Engel "Provides a new, more Java-literate way to understand the 23 GoF patterns." - Bob Hanmer "This book translates Design Patterns into what Java programmers need to know. It is full of short, engaging programming and design problems with solutions - making it easy for programmers to work through solutions and really make patterns 'stick.'" - Rebecca Wirfs-Brock "This is one exciting book. It's approachable, readable, interesting, instructive, and just plain valuable. It'll eclipse all other books purporting to teach people the GoF patterns in Java - and perhaps any other language." - John Vlissides Java programmers, you now have the resource you need to harness the considerable power of design patterns. This unique book presents examples, exercises, and challenges that will help you apply design pattern theory to real-world problems. Steve Metsker's learn-by-doing approach helps you enhance your practical skills and build the confidence you need to use design patterns effectively in mission-critical applications. Design Patterns Java Workbook features the twenty-three foundational design patterns introduced in the classic book Design Patterns (Addison-Wesley, 1995). In this new, hands-on workbook, the patterns are organized into five major categories: interfaces, responsibility, construction, operations, and extensions. Each category begins with a chapter that reviews and challenges your ability to apply facilities built into Java. These introductory sections are followed by chapters that explain a particular pattern in detail, demonstrate the pattern in use with UML diagrams and Java code, and provide programming problems for you to solve. With this book you will build expertise in important areas such as: Adapting domain data to Swing components Creating a FACADE for Swing Handling recursion in composites Understanding the role of BRIDGE in Java database connectivity Making the connection between Model/View/Controller and OBSERVER Maintaining relational integrity with a mediator Using proxies to communicate between computers Letting a service provider decide which class to instantiate Supporting undo operations with MEMENTO.